Economic evaluation of nutrition interventions: Does one size fit all?. Issue 9 (September 2021) - Fattore, Giovanni; Federici, Carlo; Drummond, Michael; Mazzocchi, Mario; Detzel, Patrick; Hutton, Zsuzsa V; Shankar, Bhavani
Highlights: Cost-utility analysis is a well-established approach to inform decision makers in the realm of health-care. There exist different types of nutrition interventions, each presenting special features that deserve attention for appropriate economic evaluations. Depending on the type of nutrition intervention standard cost-utility analyses may be inadequate and additional methodological approaches may be required. Abstract: Background: : Nutrition interventions have specific features that might warrant modifications to the methods used for economic evaluations of healthcare interventions. Aim: : The aim of the article is to identify these features and when they challenge the use of cost-utility analysis (CUA). Methods: : A critical review of the literature is conducted and a 2 by 2 classification matrix for nutrition interventions is proposed based on 1) who the main party responsible for the implementation and funding of the intervention is; and 2) who the target recipient of the intervention is. The challenges of conducting economic evaluations for each group of nutrition interventions are then analysed according to four main aspects: attribution of effects, measuring and valuing outcomes, inter-sectorial costs and consequences and equity considerations. Results and conclusions: : CUA is appropriate for nutrition interventions when they are funded from the healthcare sector, have no (or modest) spill-overs to other sectors of the economy and have only (or mainly) health consequences. For other interventions, typically involving different government agencies, with cost implications for the private sector, with important wellbeing consequences outside health and with heterogeneous welfare effects across socio-economic groups, other economic evaluation methods need to be developed in order to offer valid guidance to policy making. For these interventions, checklists for critical appraisal of economic evaluations may require some substantial changes.